Perlindungan Hukum Bagi Anak Sebagai Saksi dalam Pemeriksaan Perkara Pidana - Erwin Asmadi (Iuris Studia: Jurnal Kajian Hukum, 2020)
Law No. 11 of 2012 concerning the Juvenile Justice System explains that children have a strategic role which is explicitly stated that the state guarantees the rights of every child to survival, growth and development as well as protection from violence and discrimination. Therefore, the best interests of children should be lived out as the best interests for the survival of mankind. Law No. 23 of 2002 concerning Child Protection, explicitly explains in Article 1 Paragraph (2), "Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity. , and face violence and discrimination ”. This writing uses normative juridical legal research methods (normative research). The nature of this research is descriptive, which aims to provide an overview of social symptoms regarding the role of psychiatrists in proving psychological violence in criminal acts of domestic violence. Sources of research data are primary legal materials, secondary legal materials and tertiary legal materials. The data collection method was carried out using document study techniques, which were analyzed using qualitative analysis techniques. Based on the results of the research that children as witnesses are entitled to all protections as regulated in Law Number 11 of 2012 concerning the Child Criminal Justice System. Seen in Articles 89, 90 and 91 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System